The Effect of Perceptions of Profit Sharing, Islamic Financial Literacy, and E-Banking on Customer Interests in Using Bank Syariah Indonesia (BSI) Services Religiosity as a Moderating Variable - Maulidya, Mey; Putra, Rediyanto (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
The increasing development of Islamic banks in Indonesia can be seen in the office network of Islamic banks, which increased by 3% from 2020 to 2021. Therefore, the purpose of this study is to explain the influence of perceptions of profit sharing, Islamic financial literacy, and the quality of e-banking services on customer interest in using BSI services, with religiosity as a moderating variable. The data in this study used primary data collected by a questionnaire that was distributed to 400 BSI customer respondents determined by the Slovin formula. The sampling technique used was accidental sampling. The analysis technique in this study uses moderating regression analysis (MRA) with the help of SPSS 25. The results of this study indicate that perceptions of profit sharing, Islamic financial literacy, and quality of e-banking services have a positive influence on customers' interest in using BSI services, either partially or simultaneously; religiosity is unable to moderate the influence of perceptions of profit sharing, Islamic financial literacy, and quality of e-banking services on interest in using BSI services. The suggestion for this research is that future researchers should add other variables that affect interest in using BSI services, such as trust, brand image, and product diversity, as independent variables and make promotion variables a moderating variable to obtain more comprehensive results. They also need to add samples with wider coverage areas. wider so that it is not dominant in students so that further research can provide a broader picture of the problem of this research and the level of generalization obtained can be higher. Not only that, readers are expected to add insight regarding Islamic financial literacy and understanding of the profit-sharing system implemented by Bank Syariah Indonesia so that they have an interest in using BSI services